Van Gogh and the artists he loved - Naifeh, Steven 1952- (Random House, 2021)
"To us, Van Gogh's paintings look utterly unique. His vivid palates and wildly interpretive portraits are unmistakably his--yet however revolutionary his style may have been, it was actually built on a strong foundation of paintings by other artists, both his contemporaries and those who came before him. Now, drawing on Van Gogh's own thoughtful and often poetic comments about the artists he venerated, Steven Naifeh gives a gripping account of his deep immersion in their work. We see Van Gogh's gradual discovery of the subjects he made famous, from wheat fields to sunflowers. We watch him copying the colors used by one artist, experimenting with the thick layers of paint on canvas used by another, all vividly illustrated with 275 paintings by Van Gogh and a variety of other major artists, positioned side by side. Thanks to the vast correspondence from Vincent to his beloved brother Theo, Naifeh is able to reconstruct Van Gogh's artistic world from within. Observed in eloquent prose that is as compelling as it is authoritative, Van Gogh and the Artists He Loved enables us to share the artist's journey as he established his own audacious, influential, and widely beloved body of work"--
Includes index
Searchable bibliography and notes for book are available online
Keywords: Gogh, Vincent van -- 1853-1890; Gogh, Vincent van / 1853-1890 / Criticism and interpretation; Gogh, Vincent van / 1853-1890 / Sources; ART / General; Gogh, Vincent van / 1853-1890; History / Sources; Criticism, interpretation, etc